2021
DOI: 10.1152/japplphysiol.00892.2020
|View full text |Cite
|
Sign up to set email alerts
|

Slight power output manipulations around the maximal lactate steady state have a similar impact on fatigue in females and males

Abstract: Neuromuscular fatigue (NMF) and exercise performance are affected by exercise intensity and sex differences. However, whether slight changes in power output (PO) below and above the maximal lactate steady-state (MLSS) impact NMF and subsequent performance (time to exhaustion, TTE) is unknown. Purpose: This study compared NMF and TTE in females and males in response to exercise performed at MLSS, 10 W below (MLSS-10) and above (MLSS+10). Methods: Twenty participants (9 females) performed three 30-min constant-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
2
22
3
Order By: Relevance
“…Sex determines differences in the biological organization at all levels ( Holdcroft, 2007 ), including cardiac modulatory balance, which has been related to a greater tone in the autonomic vagal branch in females and a greater tone in the sympathetic branch in males ( Spina et al, 2019 ). As effort intensity also influences HRV recovery, it is noteworthy that females have an advantage in resistance to fatigue during submaximal contractions, with less impairment in neuromuscular activation after strenuous exercise; however, this advantage diminishes as the intensity of contractions increases ( Azevedo et al, 2021 ). Therefore, considering the differences in cardiac autonomic modulation and resistance to fatigue between males and females, muscle fatigue during a competitive period may influence cardiac autonomic control in a sex-specific manner during a competitive period in swimming athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Sex determines differences in the biological organization at all levels ( Holdcroft, 2007 ), including cardiac modulatory balance, which has been related to a greater tone in the autonomic vagal branch in females and a greater tone in the sympathetic branch in males ( Spina et al, 2019 ). As effort intensity also influences HRV recovery, it is noteworthy that females have an advantage in resistance to fatigue during submaximal contractions, with less impairment in neuromuscular activation after strenuous exercise; however, this advantage diminishes as the intensity of contractions increases ( Azevedo et al, 2021 ). Therefore, considering the differences in cardiac autonomic modulation and resistance to fatigue between males and females, muscle fatigue during a competitive period may influence cardiac autonomic control in a sex-specific manner during a competitive period in swimming athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Burnley et al (9) showed that the rate of impairments in isometric maximal voluntary torque and contractile function, measured through electrically evoked responses to relaxed muscle, was four to five times faster when performing isometric exercise moderately above versus below critical torque. Consequently, even power outputs marginally above critical power or the maximum lactate steady state (10) are associated with inexorable perturbations in metabolic homeostasis and, concurrently, impairments in neuromuscular function owing primarily to disturbances at the contractile level.…”
mentioning
confidence: 99%
“…Even though exercise intensity and duration are accepted as major contributors that determine the amplitude of decline in performance fatigability after exercise cessation (9,10), recent studies have highlighted the key role that a critical metabolic boundary such as the maximal lactate steady state (MLSS) plays on the amplitude of decline in contractile function (11,12). For example, we have recently shown that even 10-W increments or decrements in power output (PO) from the MLSS elicit greater and lower contractile function impairments after a 30-min cycling, respectively (12).…”
mentioning
confidence: 99%
“…Even though exercise intensity and duration are accepted as major contributors that determine the amplitude of decline in performance fatigability after exercise cessation (9,10), recent studies have highlighted the key role that a critical metabolic boundary such as the maximal lactate steady state (MLSS) plays on the amplitude of decline in contractile function (11,12). For example, we have recently shown that even 10-W increments or decrements in power output (PO) from the MLSS elicit greater and lower contractile function impairments after a 30-min cycling, respectively (12). However, likely because of the technical challenges associated with the evaluation of performance fatigability during exercise, a majority of studies to date have limited their measurements to task failure (10,13,14), ultimately neglecting the assessment of VA and contractile function throughout the exercise bout (i.e., time course) and at different intensities.…”
mentioning
confidence: 99%
See 1 more Smart Citation